(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Now a day, amplifiers are one which is greater in power gain. It is fundamental to modern electronics, widely used in almost all electronic equipment. The cascode amplifiers are key element to various useful circuits. It has more advantages as increasing bandwidth and high slew rate, with high gain, moderately high input impedance and higher output impedance. A recycling folded cascode amplifier (RFCA) gives improved parameters over that of the conventional folded [1]. This is obtained by using previous circuit which is idle devices in the signal path, which results in improved transconductance, gain and slew rate [1]. The cascode stage consists of a common gate and common source terminal. The complementary folded cascode amplifier (CFCA) are mirror type configured circuit, which saves its power and greater settling point. A slew rate that allows maximum frequency above the range, which will eliminates any potential errors and unwanted signal. The circuit having a slew rate above 6.3V/µs most seems as used. A unity gain bandwidth can used to amplify the signal, wider bandwidth can eliminates smaller signal.